Analisis Keterampilan Bertanya Siswa Mata Pelajaran Tematik Tema 8 Subtema 3 Kelas V SDN 2 Mojoarum - Anik Rahayuningsih; Nugraha Janattaka (Universitas PGRI Adi Buana Surabaya, 2019)
Question and answer is a major part of student learning activities. The questioning activity is askingfactual questions or hypotheses that begin with guidance from the teacher until students understandthemselves and become habitual activities. This study aims to describe the Students' Asking Skills in theEnvironment is the theme of Our Friends Sub Thematic Environmental Conservation Sub-ThematicSubjects and describe the obstacles experienced by fifth grade students of SD Negeri Mojoarum GondangTulungagung 2 class 5 in 2018/2019. The method used in this research is a qualitative descriptiveapproach. The results of this study are 7 students who have fulfilled all the requirements for questioningskills indicators, on the other hand there is one student who only reaches one point from therequirements, two questioning skills indicator requirements are met by 6 students, there are two studentswho cannot meet the indicator requirements questioning skills. The obstacles experienced by studentshave not been able to use Indonesian correctly, lack of focus in asking questions, lack of confidence, fearof being wrong, embarrassed when laughed at by their friends and unable to raise their voices so thatquestions can reach the whole class. The conclusion of this study is that each student in class VMojoarum has different questioning skills.